Discursive Representation within the Institutional Void: The Rise and Fall of a Governance Network on Sustainable Food in Belgium. Issue 3 (24th March 2017) - Crivits, Maarten; de Krom, Michiel P.M.M; Dessein, Joost; Block, Thomas
Abstract: Recently, democratic theorists have turned their attention to political representation. This renewed attention is inspired by a questioning of the formalist interpretation of representative government that presumes a strict division between elected political elites and deliberative participation in the public sphere. Several scholars argue that the standard account of representative democracy based on residence‐based and electoral representation does not suffice to explain contemporary political practice. Representation, then, becomes a 'practice' in which the object of representation and the grounds on which it is defended, co‐determine 'who' and 'what' is considered politically legitimate and how 'interests' are to be represented. In this paper we explore how discursive interaction on political representation takes place in an 'institutional void', i.e. a political setting in which there are no clear rules and norms to which politics is to be conducted. We base our analysis on an interpretative reconstruction of the rise and fall of a sustainability governance process in the Flemish agro‐food domain called the New Food Frontier (NFF). We claim to have found several interacting political conceptions, that operated on both explicit and more tacit levels, which particularly shaped the political interventions within the institutional void of the NFF. Analysis reveals that the dominant/initial conception of the studied political process has strong affinities with Dryzek's ideas on discursive representation. Competing claims on how political representation should work were linked to neo‐corporatism and transition management. We analyze how these competing conceptions play in the organization, articulation and disintegration of the governance network. Secondly, we relate this deliberative 'outcome' to the broader political setting in which the sustainability governance trajectory was embedded. In this context, a re‐negotiation of the rules of the game within a new governance setting and the relationship with institutionalized politics proved to be important factors in explaining the discontinuity of the process of discursive representation.